O papel da mulher em dona Narcisa de Villar. - Costa, Denison Soares (Universidade Federal do Tocantins, 2022)
This work analyzes the novel Dona Narcisa de Villar, wrote by Ana Luísa Azevedo Castro, the Ypiranga Indigenous. It is the novel rescued less than three decades ago, but it has been produced and released still on the nineteenth century. The study justifies by the needness to research the way as women has been viewed in their own narratives. In analyzing nineteenthcentury historiography, seldom to see any names of female authors. The proposal is to make a reflection on the representativeness of women in the mentioned work form the aim to understand how the female characters are represented in the novel and in the society. The study’s specific objectives are: to analysis of the text of the novel in question; to draw attention to the importance to study forgotten works of female authorship; to reflect on the role of women in literature and society. A methodology adopted was bibliographic survey as support for the female roles observed in this novel. The results of this work through these revealed studies proved that women have been victims of several battles in their struggle for freedom and recognition. Adctionally, it is thanks to the persistence and collective engagement, the woman has been able again to rewrite her role in history